Preparation of new halogenated diphenyl pyrazine analogs in Escherichia coli by a mono-module fungal nonribosomal peptide synthetase from Penicillium herquei. Issue 32 (8th August 2018) - Yang, Can; Xu, Yuanyuan; Xu, Kangping; Tan, Guishan; Yu, Xia
Graphical abstract: Highlights: The biocatalytic approaches to obtain diphenyl pyrazine analogs. Exploration of the catalytic ability of HqlA towards tyrosine derivatives. The potential usage of HqlA as biocatalyst to synthase substituted pyrazines. Abstract: Pyrazines are important structures widely found in many known drugs. The biological approaches for their synthesis were poorly applied. Herein, microbial production of several halogenated diphenyl pyrazines is reported. These compounds are accumulated via feeding corresponding precursor analogs to Escherichia coli expressing a fungal non-ribosomal peptide synthetase HqlA. Substrate specificity of HqlA was also determined by comparing substrate incorporation efficiencies. HqlA requires a C4-hydroxyl in the substrate and can tolerate certain degrees of size change on the substitution at the carbon next to the hydroxyl group.